2000
DOI: 10.1016/s0306-4522(00)00089-0
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle number does not predict postsynaptic measures of miniature synaptic activity frequency in cultured cortical neurons

Abstract: Abstract-We tested the hypothesis that heterogeneity in the frequency of miniature synaptic activity reflects differences in the number of vesicles present in presynaptic terminals. Using imaging techniques, we measured dendritic miniature synaptic calcium transients attributed to the spontaneous release of single transmitter quanta. Following imaging, the identified neurons were processed for serial transmission electron microscopy. At sites of quantal Ca 2ϩ transients mediated by N-methyl-d-aspartate recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Data on spontaneous release frequencies of vesicles are still scarce and we found only one such study (Mackenzie et al, 2000 ). Experimentally, the maximum spontaneous vesicle release rate found was 0.25 Hz.…”
Section: Methodsmentioning
confidence: 90%
“…Data on spontaneous release frequencies of vesicles are still scarce and we found only one such study (Mackenzie et al, 2000 ). Experimentally, the maximum spontaneous vesicle release rate found was 0.25 Hz.…”
Section: Methodsmentioning
confidence: 90%
“…Furthermore, synaptic density in cultured cells is considerably lower than that found in vivo, reducing the likelihood of signal spillover. In previous studies using dissociated cultures, we reconstructed sites of MSCTs and found that most Ca 2ϩ transient initiation sites were associated with a single presynaptic terminal (Mackenzie et al, 2000); however, it is conceivable that some differences in Ca 2ϩ transient frequency may be caused by differences in synapse or release site number. Line-plot analysis of Ca 2ϩ -induced changes in fluorescence during repeated MSCTs indicated little spatial variation (within the limits of light microscopy and our imaging conditions) with regard to Ca 2ϩ transient initiation points during multiple events at presumably the same synapse (Fig.…”
Section: Imaging Of Asynchronous Postsynaptic Activity After Train Stmentioning
confidence: 99%
“…This noise could not only influence the synaptic variability, but also the transmission of information (Jacobson et al, 2005). Thus, while some studies do not support our hypothesis of the contribution of the number of vesicles in synaptic noise (Mackenzie et al, 2000), several others (Korn et al, 1993; Franks et al, 2003; Faisal et al, 2008; Pulido and Marty, 2017) inspired us to include additional synaptic noise in our model. Finally, we also validated our method by building three different in silico data sets where the mean N RRP was set to 1, 4 and 10, respectively.…”
Section: Discussionmentioning
confidence: 79%